If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -8 = -7x + 1 Reorder the terms: -8 + 3x = -7x + 1 Reorder the terms: -8 + 3x = 1 + -7x Solving -8 + 3x = 1 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. -8 + 3x + 7x = 1 + -7x + 7x Combine like terms: 3x + 7x = 10x -8 + 10x = 1 + -7x + 7x Combine like terms: -7x + 7x = 0 -8 + 10x = 1 + 0 -8 + 10x = 1 Add '8' to each side of the equation. -8 + 8 + 10x = 1 + 8 Combine like terms: -8 + 8 = 0 0 + 10x = 1 + 8 10x = 1 + 8 Combine like terms: 1 + 8 = 9 10x = 9 Divide each side by '10'. x = 0.9 Simplifying x = 0.9
| 3x-4yi=4+4i | | 2x^3=26 | | -2-16=3h-6 | | 2g-3=-19+g | | X+x+1=69 | | 2x+3=5-4x | | (x-7)(x+6)= | | 4x+20=12x+84 | | -2(4b+1)+(9b-6)=0 | | 8p-6-3p+2=15+2p+2 | | (-2x^3+4)(2x^2+5)= | | 13-10x=43-24x | | 3y-12=2(2y+44) | | (3x-3)(x-9)= | | 4(5+2)+2= | | 15x-28=-73 | | =-4x^2+5x-12 | | 7-1k=5+3k | | 18g+7=14g-9 | | 8x-12=3x+11 | | =4x^2-5x+12 | | 5a-8a+3a= | | -2d+18-4d=16 | | 2+3y=8 | | 3.3q-2.9-4.8q=2.5q-4.9 | | 6+b=7 | | 15d-8-3d=16 | | (2x^3+3x^2-1)=0 | | (3b-2)(3b^3+6b^2+2)= | | 7x=14+15x | | 4(y+4)=5(y-3) | | 6.7+12m-9.3=6.2 |